Spatially well-defined carbohydrate nanoplatforms: synthesis, characterization and lectin interaction study. Issue 83 (29th September 2016) - Timmer, B. J. J.; Flos, M. Abellán; Jørgensen, L. Mønster; Proverbio, D.; Altun, S.; Ramström, O.; Aastrup, T.; Vincent, S. P.
Abstract : Two novel dodecasubstituted carbohydrate nanoplatforms have been prepared for use in evaluating the importance of the spatial distribution of carbohydrates in their interaction with lectins. Abstract : Two novel dodecasubstituted carbohydrate nanoplatforms based on molecular Borromean rings and dodecaamine cages have been prepared for use in evaluating the importance of the spatial distribution of carbohydrates in their interaction with lectins. The binding affinities of the glyconanoplatforms were characterized using quartz crystal microbalance technology and compared with a monovalent reference and dodecaglycosylated fullerenes.